The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1016/j.bbmt.2004.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Umbilical cord blood transplantation in adults: Results of the prospective cord blood transplantation (COBLT)

Abstract: The Cord Blood Transplantation study group conducted a prospective study of unrelated cord blood transplantation (CBT) to better define the role of this stem cell source for subjects requiring unrelated allogeneic transplantation. We report on 1 stratum of the study designated for adult subjects. The primary end point of the study was survival at 180 days. Secondary end points included engraftment, graft-versus-host disease, relapse, and long-term survival. Eligibility criteria for malignant and nonmalignant d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
98
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(103 citation statements)
references
References 36 publications
4
98
0
1
Order By: Relevance
“…UCB is enriched with haematopoietic progenitor cells and contains sufficient numbers of HSCs to reconstitute most paediatric patients. 1,2,4,6,8,9,17,19,[26][27][28][29][30][31][32][33] Most studies have shown that the nucleated cell dose is of paramount importance for haematopoietic recovery, 2,4,6,14,16,17 Wagner et al 10 have also shown the CD34 cell dose as being a significant variable not only for haematopoietic recovery but also for survival. The importance of CD34 cell dose has been replicated in other studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…UCB is enriched with haematopoietic progenitor cells and contains sufficient numbers of HSCs to reconstitute most paediatric patients. 1,2,4,6,8,9,17,19,[26][27][28][29][30][31][32][33] Most studies have shown that the nucleated cell dose is of paramount importance for haematopoietic recovery, 2,4,6,14,16,17 Wagner et al 10 have also shown the CD34 cell dose as being a significant variable not only for haematopoietic recovery but also for survival. The importance of CD34 cell dose has been replicated in other studies.…”
Section: Discussionmentioning
confidence: 99%
“…2,10,11,21,23,34,36 TRM in adult recipients of UCB after a myeloablative regimen has been reported to be as high as 60%. 7,10,14,17,19,[30][31][32][33] Comparing UCBT to BMT, Rocha et al 22 compared the outcomes of 541 children transplanted for the treatment of acute leukaemia receiving a UCBT (n ¼ 99), unmanipulated BMT (n ¼ 262), or T-cell-depleted BMT (n ¼ 180). UCB recipients were observed to have a higher TRM within the early period after transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Long et al [17] noted that infection was the primary cause of death in their study of 57 adults with high-risk disease who were transplanted with unrelated UCB. A large multicenter prospective study of UCB transplantation in adults found that in 34 patients 90% experienced infections; two thirds of those studied reported at least 3 infections during the first 6 months post-transplant [19]. These authors suggested that the delay in immune reconstitution in UCB transplant patients versus BMT recipients could play a major role in their increased susceptibility to infection.…”
Section: Transplantation With Ucb : Clinical Studiesmentioning
confidence: 99%
“…[5][6][7][8] Early experience in adult CB transplantation (CBT) was hampered by poor engraftment and immune recovery. [9][10][11] Recent experience with better risk patients, double CB unit transplants and submyeloablative preparative regimens have been more encouraging. [12][13][14] There are several important differences between BM or G-CSF-mobilized PBPC and CB when selecting donors/ products for transplantation.…”
Section: Introductionmentioning
confidence: 99%